Kynurenine Metabolism Lifespan Extension Mediated by Oxidative Stress Response and Hypoxic Response in C. elegans. (17th December 2021) - Castro-Portuguez, Raul; Meyers, Jeremy; Freitas, Sam; Dang, Hope; Turner, Emily; DeNicola, Destiny; Espejo, Luis; Sutphin, George
Abstract: Aging is characterized by a progressive decline in the normal physiological functions of an organism, ultimately leading to mortality. Metabolic changes throughout the aging process disrupt the balance and homeostasis of the cell. The kynurenine metabolic pathway is the sole de novo biosynthetic pathway for producing NAD+ from ingested tryptophan. Altered kynurenine pathway activity is associated with both aging and a variety of age-associated diseases, and kynurenine-based interventions can extend lifespan in Caenorhabditis elegans. Our laboratory recently demonstrated knockdown of the kynurenine pathway enzymes kynureninase (KYNU) or 3-hydroxyanthranilic acid dioxygenase (HAAO) increases lifespan by 20-30% in C elegans. However, the mechanism of how these interventions may modulate response against different stressors during the aging process has yet to be explored. Fluorescent reporter strains show the stress-responsive transcription factors skn-1 (ortholog of NRF2/NFE2L2; oxidative stress response) and hif-1 (ortholog of HIF1A; hypoxic stress response) to be highly upregulated when the kynurenine pathway is inhibited. We also demonstrated the increase expression of gst-4 and gcs-1 (transcriptional targets skn-1), which are involved in production of the antioxidant glutathione (GSH), as well as upregulation of cysl-2 (transcriptional target of hif-1), a regulator of cysteine biosynthesis from serine. We hypothesize that lifespan extension resulting from kynurenine pathway inhibition is mediated, at least in part, by upregulation of these transcription factors, providing elevated defense against oxidative stress and hypoxic stress.